Photomechanical Actuation of Ligand Geometry in Enantioselective Catalysis1. Issue 52 (30th October 2014) - Kean, Zachary S.; Akbulatov, Sergey; Tian, Yancong; Widenhoefer, Ross A.; Boulatov, Roman; Craig, Stephen L.
Abstract A catalyst that couples a photoswitch to the biaryl backbone of a chiral bis(phosphine) ligand, thus allowing photochemical manipulation of ligand geometry without perturbing the electronic structure is reported. The changes in catalyst activity and selectivity upon switching can be attributed to intramolecular mechanical forces, thus laying the foundation for a new class of catalysts whose selectivity can be varied smoothly and in situ over a useful range by controlling molecular stress experienced by the catalyst during turnover. Forces on the order of 100 pN are generated, thus leading to measurable changes in the enantioselectivities of asymmetric Heck arylations and Trost allylic alkylations. The differential coupling between applied force and competing stereochemical pathways is quantified and found to be more efficient for the Heck arylations.